1984
DOI: 10.1161/01.cir.70.4.533
|View full text |Cite
|
Sign up to set email alerts
|

Postural changes in diastolic blood pressure and the risk of myocardial infarction: the Normative Aging Study.

Abstract: To assess the relationship of postural changes in blood pressure to risk of myocardial infarction, 1359 men were followed for an average of 8.7 years. The men were participants in the Normative Aging Study, a longitudinal study of aging initiated in 1963 at the Veterans Administration Outpatient Clinic in Boston. It was found that the relationship of sitting blood pressure to the subsequent incidence of myocardial infarction was modified by a variable formed by subtracting supine from standing diastolic blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
28
1
1

Year Published

1987
1987
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 17 publications
3
28
1
1
Order By: Relevance
“…Few prospective studies have evaluated the association of OH with stroke, although several have evaluated the association between OH and various vascular outcomes 24,25,29 or allcause mortality. 26 -28 In 2 studies, OH was related to coronary heart disease 24 and all-cause mortality 28 independently of other risk factors.…”
Section: Oh As a Risk Factor For Ischemic Strokementioning
confidence: 99%
See 1 more Smart Citation
“…Few prospective studies have evaluated the association of OH with stroke, although several have evaluated the association between OH and various vascular outcomes 24,25,29 or allcause mortality. 26 -28 In 2 studies, OH was related to coronary heart disease 24 and all-cause mortality 28 independently of other risk factors.…”
Section: Oh As a Risk Factor For Ischemic Strokementioning
confidence: 99%
“…9,21,22 One cross-sectional study that evaluated 3 definitions of OH suggested that each type of OH identifies a population subgroup characterized by different sets of risk factors. 23 Longitudinal studies evaluating OH and cardiovascular disease 24,25 or mortality 26 -29 include the Honolulu Heart Study, in which both systolic and diastolic OH were predictive of all-cause mortality, 28 and a Finnish study in which only diastolic OH was associated with increased vascular mortality. 29 OH is not even listed as a potential risk factor for stroke in several reviews, 3,4,6 and most prospective investigations of stroke have not evaluated OH as a risk factor.…”
mentioning
confidence: 99%
“…These include pulse and mean arterial pressure4 and postural changes in blood pressure. 13 When a person assumes the upright posture, cardiovascular adjustments occur to maintain the blood pressure. These actions include reflex arteriolar and venous constriction, reflex acceleration of heart rate, increase in muscle tone, and an immediate increase in plasma catecholamines.…”
mentioning
confidence: 99%
“…Studies of the association between blood pressure reactivity and the subsequent development of hypertension [1][2][3][4][5] and coronary heart disease (CHD) or stroke [6][7][8][9] have been inconclusive. Associations with elevated serum cholesterol (eg Vogele 10 and Bardwell et al 11 ), fasting glucose levels/insulin sensitivity, 11,12 and atherosclerosis 13 also have been inconsistent.…”
Section: Introductionmentioning
confidence: 99%